Pensamiento dramático y razón poética. La filosofía adentrada en el oscuro corazón del bosque - Sevilla Fernández, José Manuel (Bollettino Filosofico, 2017)
In the light of a new “southern” style of thought (meridional or mediterranean philosophy), this essay deepens into the concept of a “problematic and narrative reason”, and leads the meditation about “poetical reason” to a more concrete, practical and vital perspective: the work of dramatic art. The aim of this essay is to bring “poetical reason” closer to the dimension of “dramatic reason” and to the criticism that it raises, which is open to a true way of knowing. Authors such as Gracián, Vico, Ortega, Santayana or Zambrano and recurrent; but also poets and dramatists, who show us the poetic, vital and, eventually, dramatic aspect of reason. Special attention is paid to the Spanish dramatist José Luis Alonso de Santos and his dramatic work The Dark Heart of the Forest.